2022
DOI: 10.1093/brain/awac446
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental effects of genetic frontotemporal dementia in young adult mutation carriers

Abstract: While frontotemporal dementia (frontotemporal dementia) has been considered a neurodegenerative disease that starts in mid-life or later, it is now clearly established that cortical and subcortical volume loss is observed more than a decade prior to symptom onset and progresses with aging. To test the hypothesis that genetic mutations causing frontotemporal dementia have neurodevelopmental consequences, we have examined the youngest adults in the GENFI cohort of pre-symptomatic frontotemporal dementia mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 70 publications
2
4
0
Order By: Relevance
“…In fact, at the presymptomatic stage, we found that irrespective of the TMEM106B genotype, the presence of C9orf72 is associated with lower gray matter volumes in comparison to clinically normal nonmutation carriers, consistent with prior work showing structural brain changes occurring 10 to 40 years before onset 27,40,44 . In GRN mutation carriers, on the other hand, changes in brain volume occur only within a few years proximity to onset of symptomatic FTD 27,41,42,44 . Moreover, while the rate of volume loss differs between C9orf72 and GRN, with attenuated atrophy rate after onset of symptomatic FTD in C9orf72 and with an acceleration of atrophy rate after onset in GRN, their rate of functional decline is similar 42 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In fact, at the presymptomatic stage, we found that irrespective of the TMEM106B genotype, the presence of C9orf72 is associated with lower gray matter volumes in comparison to clinically normal nonmutation carriers, consistent with prior work showing structural brain changes occurring 10 to 40 years before onset 27,40,44 . In GRN mutation carriers, on the other hand, changes in brain volume occur only within a few years proximity to onset of symptomatic FTD 27,41,42,44 . Moreover, while the rate of volume loss differs between C9orf72 and GRN, with attenuated atrophy rate after onset of symptomatic FTD in C9orf72 and with an acceleration of atrophy rate after onset in GRN, their rate of functional decline is similar 42 .…”
Section: Discussionsupporting
confidence: 90%
“…In C9orf72 we did not observe an association between TMEM106B and (sub)cortical atrophy. In fact, at the presymptomatic stage, we found that irrespective of the TMEM106B genotype, the presence of C9orf72 is associated with lower gray matter volumes in comparison to clinically normal nonmutation carriers, consistent with prior work showing structural brain changes occurring 10 to 40 years before onset 27,40,44 . In GRN mutation carriers, on the other hand, changes in brain volume occur only within a few years proximity to onset of symptomatic FTD 27,41,42,44 .…”
Section: Discussionsupporting
confidence: 90%
“…Recent evidence showed neurodevelopmental consequences triggered by structural changes of MAPT and subsequently cortical morphology. 42 , 43 Similarly, neurodevelopmental evidence was also reported for KMT2E , 44 HTT 45 and FOXO3 . 46 Nevertheless, all the novel loci need replication and further investigation in future studies of RD.…”
Section: Discussionmentioning
confidence: 62%
“…Moreover, MRI volumes had lower diagnostic accuracy for prodromal conversion, which may be due to relative volume deficits early on in some of the participants who did not convert, as reported before especially for C9orf72 and MAPT presymptomatic carriers. 18,34,35 A previous study found that NfL and MRI changes occur closely to each other across all FTD genetic groups, 12 by modeling cross-sectional data over participant age in carriers vs controls of the same age. 12 Here, conversely, we aimed to specifically highlight the changes observable within the risk age range in carriers who convert compared with those further away from conversion.…”
Section: Discussionmentioning
confidence: 99%